Development of SLA Monitoring Tools Based on Proposed DMI in Cloud Computing - Jamail, Nor Shahida Mohd; Atan, Rodziah; Abdullah, Rusli; Said, Mar Yah (Transactions on Engineering and Computing Sciences, 2015)
Service level agreement (SLA) is a contract between service provider and user about the quality of service (QoS) in cloud computing. The cost value and benefit value of SLA monitoring systems is a concerned issue in cloud computing. The trustable SLA monitoring model is important to assess SLA validation in cloud computing. The optimization of monitoring interval is another objective of study to economize SLA monitoring system. Therefore in this paper the SLA monitoring tools is developed to evaluate the proposed dynamic interval in actual testbed of cloud computing. The experiment design described in this paper presents the cloud configuration and environmental setup for testbed experiment.